Distribución de especies de matorral en suelos ácidos y básicos de la Sierra de Grazalema, sur de España - Gallego Fernández, Juan Bautista (Anales del Jardín Botánico de Madrid, 2002)
The presence of Mediterranean shrubland woody species on acid or basic soils was studied at Grazalema Mountains. Transects were made at 137 sampling sites in the study área and 74 species were recognized. Phlomis purpurea. Cistus albidus. Quercus rotundifolia and Ulex baeticus were the most frequent species, being present at 70 % of the transects. Pistacia lentiscus. Rubia peregrina and Daphne gnidium were found in 50 % of the transects. From the total species recorded, 67 species were located on basic soils and 55 on acid soils; 19 species (25.7 %) were located only on basic soils and 7 species (9.5 %) only on acid soils; 21 species were significantly more frequent on basic soils, and 10 species on acid soils. The number of species per transect were significantly higher on basic soils (13.2 ± 3.8) than on acid soils (10.3 ± 3.7). Differences in species number are related to a higher number of species displaying a narrow distribution in the basic shrublands as well as due to species loss in the acid shrublands, as a consequence of geographic isolation and human disturbance.
Keywords: Betic ranges; Mediterranean shrubland; soil pH

Distribución de especies de matorral en suelos ácidos y básicos de la Sierra de Grazalema, sur de España - Gallego Fernández, Juan Bautista (Anales del Jardín Botánico de Madrid, 2002)
The presence of Mediterranean shrubland woody species on acid or basic soils was studied at Grazalema Mountains. Transects were made at 137 sampling sites in the study área and 74 species were recognized. Phlomis purpurea. Cistus albidus. Quercus rotundifolia and Ulex baeticus were the most frequent species, being present at 70 % of the transects. Pistacia lentiscus. Rubia peregrina and Daphne gnidium were found in 50 % of the transects. From the total species recorded, 67 species were located on basic soils and 55 on acid soils; 19 species (25.7 %) were located only on basic soils and 7 species (9.5 %) only on acid soils; 21 species were significantly more frequent on basic soils, and 10 species on acid soils. The number of species per transect were significantly higher on basic soils (13.2 ± 3.8) than on acid soils (10.3 ± 3.7). Differences in species number are related to a higher number of species displaying a narrow distribution in the basic shrublands as well as due to species loss in the acid shrublands, as a consequence of geographic isolation and human disturbance.
Keywords: Betic ranges; Mediterranean shrubland; soil pH

Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B; Gómez-Gutiérrez, J M; Moreno-Marcos, G (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling

Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B.; Gómez-Gutiérrez, J. M.; Moreno-Marcos, G. (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling